The Absence of Generosity and Obedience to Authority: Judgments of Teachers and Students From Kindergarten - Kawashima, Rosana Akemi; Martins, Raul Aragão (Paidéia (Ribeirão Preto), 2015)
Preschool Education can provide conditions for the construction of moral values in children. This study’s objective was to investigate the judgment of teachers and students in Primary Education regarding the virtue of generosity and whether, in this judgment, it is valued more than obedience to authority. Interviews were held with 26 teachers and 90 children from four municipal schools, using a stimulus-story about an activity using modeling clay. The results indicated that, for the majority of participants, the attitude of the teacher in the stimulus-story, in not helping the child and demanding obedience in first place, is wrong. In relation to the reasons, for the majority of the teachers, the lack of help is justified because the activity with the modeling clay should be free, prioritizing the child’s wishes. For the majority of the children, however, the teachers’ lack of help is felt as failure to attribute postive value. Furthermore, it was observed that the strength of the virtue of generosity among the participants in this study is weak.